Grisel Syndrome as a Complication of a Parapharyngeal Abscess - Medeiros, Nuno; Valente, Pedro; Aguiar, Cristina; Larangeiro, João; Condé, Artur (Gazeta Médica, 2021)
INTRODUCTION: Grisel syndrome is a rare entity that corresponds to a non-traumatic atlantoaxial rotatory subluxation, usually secondary either to an infection of the upper airway or to a head and neck procedure. Patients usually present with torticollis, and a high index of suspicion is needed for correct diagnosis. CASE REPORT: A 6-year-old boy was admitted to the ER with sore throat, fever, and torticollis. Clinical examination revealed neck flexion with rotation to the right. Computed tomography scan revealed a parapharyngeal abscess and an anterior displacement of the atlanto-axial joint of 3 mm, configuring a type II of Fielding. The child was admitted for endovenous antibiotic treatment, surveillance, and cervical immobilization. DISCUSSION: Grisel syndrome may present in a child with torticollis and neck infection. Otorhinolaryngologists should remember the possible presentations and risk factors for this syndrome. Conservative treatment is often enough, and early identification and immobilization seem to lead to better outcomes.